Halal Social Media Marketing Activities on Wardah Halal Cosmetic - Purnomowati, Indah (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2024)
This study aims to describe the halal social media marketing activities related to Wardah halal cosmetics. It examines how these marketing activities influence consumer loyalty and the quality of relationships with cosmetic buyers. The research was conducted among consumers at cosmetic retail stores using purposive sampling, with 200 respondents. Data analysis was performed using Structural Equation Modeling via the LISREL application. The findings indicate that halal social media marketing activities can foster a strong quality of relationship with Muslim women. Furthermore, consumer loyalty has a greater impact on halal social media marketing activities than relationship quality. This suggests that satisfaction with the Islamic values inherent in halal products and their marketing methods, which align with Islamic principles, particularly appeals to Muslim women. This study provides insights for Wardah Halal Cosmetics to consistently uphold halal values in product quality and apply social media marketing under Islamic law